Sports Diplomacy and International Relations: A case study for the Winter Olympic Games of Pyeongchang 2018 and the Public relations between North Korea and South Korea - Villalpando Moreno, Laura Monica (Πανεπιστήμιο Πελοποννήσου, 2021)
Sports diplomacy as a tool for soft diplomacy within the international scenario has shown to be able to enhance relations between States by using sports events as non-official venues for political and international leaders. Within the Olympic Games, some cases of sports diplomacy can be found and as the best example is the well-known Ping-Pong diplomacy. This thesis reviews the use of sports diplomacy during the Winter Olympic Games of Pyeongchang 2018, and how the sports event was a tool that contributed to the forthcoming talks between South Korea and North Korea after years of zero relation.
Keywords: Diplomacy - Social aspects; Diplomacy - Case studies; Diplomacy and foreign policy; International relations - Case studies; Olympics; Διπλωματία - Κοινωνικές απόψεις; Διπλωματία - Περιπτωσιολογικές μελέτες; Διπλωματία και εξωτερική πολιτική; Διεθνείς σχέσεις - Περιπτωσιολογικές μελέτες; Ολυμπιακοί αγώνες; Diplomacy; International relations; Sports; Olympic Games; Korean peninsula